2007
DOI: 10.1103/physrevb.75.233406
|View full text |Cite
|
Sign up to set email alerts
|

Surface termination of hematite at environmental oxygen pressures: Experimental surface phase diagram

Abstract: International audienceWe provide an experimental surface phase diagram (surface termination versus chemical oxygen potential) of alpha-Fe2O3(0001) using a natural single crystal surface. In a partial reduction reoxidation cycle, we observe a sequence from oxygen-, to ferryl-, and again oxygen-terminated surfaces, in better agreement with recent density functional theory in the generalized gradient approximation calculations than with calculations taking into account on-site Fe 3d Coulomb repulsion. The nonreve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(99 citation statements)
references
References 24 publications
(38 reference statements)
6
92
1
Order By: Relevance
“…a-Fe 2 O 3 (0 0 0 1) surface structure Previous studies of the hydrated a-Fe 2 O 3 (0 0 0 1) surface have indicated the co-existence of chemically distinct domains (Eggleston et al, 2003;Trainor et al, 2004). The relative proportions of distinct domains and/or the presence of a single dominant chemical domain likely depends on the surface preparation conditions (Tanwar et al, 2007a), and the chemical environment of the system (Wang et al, 1998;Chambers and Yi, 1999;Shaikhutdinov and Weiss, 1999;Eggleston et al, 2003;Bergermayer et al, 2004;Trainor et al, 2004;Lemire et al (2005), Barbier et al, 2007). Therefore, prior to analysis of the Fe(II) reacted surface, the identification of the surface structure of the sample under consideration following the preparation procedure described above was essential.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…a-Fe 2 O 3 (0 0 0 1) surface structure Previous studies of the hydrated a-Fe 2 O 3 (0 0 0 1) surface have indicated the co-existence of chemically distinct domains (Eggleston et al, 2003;Trainor et al, 2004). The relative proportions of distinct domains and/or the presence of a single dominant chemical domain likely depends on the surface preparation conditions (Tanwar et al, 2007a), and the chemical environment of the system (Wang et al, 1998;Chambers and Yi, 1999;Shaikhutdinov and Weiss, 1999;Eggleston et al, 2003;Bergermayer et al, 2004;Trainor et al, 2004;Lemire et al (2005), Barbier et al, 2007). Therefore, prior to analysis of the Fe(II) reacted surface, the identification of the surface structure of the sample under consideration following the preparation procedure described above was essential.…”
Section: Resultsmentioning
confidence: 98%
“…A possible reversible conversion of an Fe-layer termination to a ferryl termination due adsorption and desorption of oxygen has been proposed by Jarvis and Chaka (2007). In comparison, recent experimental work on natural single crystals of a-Fe 2 O 3 (0 0 0 1) suggest that the surface stoichiometry is consistent with the O-layer termination at 573 K and oxygen pressure of 10 À7 -10 3 mbar (Barbier et al, 2007), while at a temperature of 773 K, the ferryl termination was observed at oxygen pressures in range of 10 -6 -10 3 mbar (Barbier et al, 2007).…”
Section: Introductionmentioning
confidence: 92%
“…This gives an atomistic description of the process forming the experimentally [20,24] found Fe=O sites that have been shown to be stable in vacuum [63] even though hydroxylated surfaces have been estimated to be more stable in aqueous conditions [25]. Other experiments support the formation of Fe=O sites for low water coverage [64] since this correlates with reduced hydroxyl group coverage [65], which explains why this behaviour is observed for the iron termination only since the oxygen terminated surface has a high water coverage (see figure 4).…”
Section: Autoionizationmentioning
confidence: 99%
“…Hartree-Fock calculations) or experimental results 15,158 . It can be possible that the corrections that best describe bulk and surface properties are different, as one value is typically not optimal for all properties 156,159,160 . In that case not taking the difference into account could affect simulation results, as demonstrated by recent studies about OER on hematite surface [156][157][158] .…”
Section: Practical Limitations Of Density Functional Theory Calculationsmentioning
confidence: 99%
“…In that case not taking the difference into account could affect simulation results, as demonstrated by recent studies about OER on hematite surface [156][157][158] . Pure DFT has been considered to describe the surface properties of hematite better than DFT+U although this may not actually be the case 156,159,160 . Nevertheless, it has been used to study OER on hematite surfaces, and compared with DFT+U the simulations yielded significantly different free energy changes for the reaction steps, and even a different RLS for the same surface on one occasion [156][157][158] .…”
Section: Practical Limitations Of Density Functional Theory Calculationsmentioning
confidence: 99%